Design of Wastewater Collection Network and Stormwater drainage Network for Bait Wazan village - Dawla Najjar; Rawand Sha3ar; Beesan Jamal (My University, 2014)
Water is most important for the life of human beings. When water is being used it becomes wastewater. Wastewater is produced from different sources such as domestic, commercial and industrial activities .Water consumption rate, population density, industrial practices and social habits influence the characteristics of wastewater. The common practice is to dispose of the wastewater using cesspits. However, the cesspits harm the environment since cesspits pollute groundwater and soil, create bad odors, and cause economic losses due to evacuation costs. The wastewater network collection is an ideal way for the disposal of wastewater since it conveys it to the wastewater treatment plant. The treatment makes wastewater to be acceptable to the environment to be used in agriculture and industry. So SewerCAD , which is one of specialized water software, will be utilized to make design of wastewater collection network for the study area that we have selected. We get water normally by rainfall that reaches the surface of the ground. But some time the rain turn into runoff when it falls into the roof of building and then leaks into the street. The dangerous case when the rain falls in high intensity in a short duration which causes many problems that includes the difficulty and loss of movement of people and damage to the streets in addition to the economic losses . To make these problems under control we must construct a stormwater collection network. In order to do that we have to do a design of such a network. This design should be according to the hydraulic concepts. However when having large areas we need to find convincing and efficient ways to do the design. So StormCAD, which is one of specialized water software, will be utilized to make a design of a stormwater collection network for the study area that we have selected. The study area (Bait Wazan Village) was selected and is located in the north part of the West Bank, 4 km northwest of Nablus City. The reasons behind selecting this area were the same as pointed out previously. In addition to that, this area is exposed to significant population growth and fast urban expansion  Moreover it is a steep area at this time expected to yield  a large amount of runoff in order to that we want to make a network for it. Beit Wazan is one of the Palestinian villages which do not have any infrastructure such as wastewater collection network  and stormwater collection network  .  1.2. Objectives The main objectives  of the project are to design the following   network  for Beit Wazan Village: 1-      Wastewater collection network using SewerCAD. 2-     Stormwater collection network using StormCAD.